Knowledge and practice on first aid of rice (rest, ice, compression, elevation) method among undergraduate nursing students in Universiti Sains Malaysia - Zahari, Muhammad Faizal Che (Universiti Sains Malaysia, 2025)
Musculoskeletal injuries, like sprains and strains, are common in both clinical and community settings. The RICE method (Rest, Ice, Compression, Elevation) is a widely used first aid approach to manage these injuries effectively. As future healthcare providers, nursing students need the knowledge and skills to use this method properly, emphasizing the importance of nursing education in early injury management. This study aimed to assess the level of knowledge and practice of the RICE method among undergraduate nursing students at Universiti Sains Malaysia (USM), and to explore the relationship between knowledge, practice, and selected socio-demographic factors. A cross-sectional study was carried out using a structured questionnaire, with 190 students taking part. Data were analysed using descriptive statistics, Pearson correlation, and Chi-Square tests with SPSS version 28.0. Most students (n = 118, 62.1%) had adequate knowledge of the RICE method, and 60.5% (n = 115) showed good practice. A significant positive correlation was found between knowledge and practice (r² = 0.337, p = 0.01). Among socio-demographic factors, only age showed a significant link with knowledge (χ² = 7.745, p = 0.021), while gender, education level, and prior exposure did not show significant associations